PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN NILAI-NILAI KEISLAMAN DI SEKOLAH TERHADAP PRESTASI KERJA GURU - Taryaman Taryaman (Asaatidzah, 2022)
The factor of principal leadership and islamic values ​​in schools becomes a key element in improving the work performance of teachers. Educational leadership as an ability to influence the process, coordinate, mobilize others that have something to do with the development of science of education and implementation of education and teaching so that activities can be run more effectively and efficiently in the attainment of educational goals and teaching. The purpose of this article is to discuss the influence of principal leadership and Islamic values at school toward teacher`s work performance. Discussion of the methodology used in this article are effectual causal analysis approach with a discussion using qualitative methods, complemented by observations and interviews as a research instrument. The authors tend to see that the work achievement/performance/productivity is influenced by the values ​​established, especially the value of sincerity. The more sincere a teacher will create a better performance. Work performance and the internalization of the values ​​will be able to be created by the pattern of school leadership. The results of the discussion show that the school leadership affect the internalization of religious values in sustaining/improving work performance of teachers.